Description Analysis of Human Behavior that Causes the Emergence of HIV/AIDS Infectious Diseases in Surabaya - Susilawati, Yayuk; Nasronudin, Nasronudin; atika, atika (Institute of Topical Disease Universitas Airlangga, 2010)
HIV virus is transmitted to other individuals particularly through sexual contact with infected individuals, narcotic abuse using shared infected needle, maternal-fetal transmission in perinatal period, either during pregnancy, labor, and breastfeeding, or through infected blood donor. The diagnosis of HIV/AIDS infection is established using laboratory examination with the indication of clinical symptoms or high risk behavior. This descriptive study was intended to describe human behaviors that cause the occurrence of HIV/AIDS in Surabaya. To find the description of the disease, the percentage of total HIV/AIDS patients according to behavioral risk factors was estimated. Total patients in 9 hospitals at each risk factor were divided with total patients in those hospital, multiplied with 100. The description of the disease according to behavioral risk factors in Surabaya is as follows: total patients between January and December 2005 was 382 individuals; 204 due to sexual contact (53.40%), 161 due to injected drug use (IDU) (42.15%), 6 perinatal cases (1.57%) and 11 with unknown causes (2.88%). From risk factor sexual relationship behavior as many as 204 people, respectively heterosexual 174 people (85.29%), homosexual 17 people (8.33%) and bisexual 13 people (6.37%). Further analytical studies are needed to analyze correlation between human behavior and the occurrence of HIV/AIDS in Surabaya.